Upaya Meningkatkan Hasil Belajar Peserta Didik Melalui Penerapan Model Pembelajaran Group Investigation Pada Mata Pelajaran Ilmu Pengetahuan Alam Dan Sosial Dan Sosial Kelas VI SDN Harjasari 1 Kota Bogor - Rifani Priharyanti; Supardi U.S (Lembaga Pengembangan Kinerja Dosen, 2025)
Getting satisfactory student learning outcomes is the most expected goal by all teachers. However, if the reality is not as expected, especially in elementary school units, of course, teachers' steps do not stop to improve and achieve the main goal. That is what happened to students in grade VI of SDN Harjasari 1, South Bogor District, Bogor City, where the Writer is assigned. The lack of student learning activities in the classroom is the main cause of not getting maximum learning results. For this reason, the author conducted research by applying the Group Investigation Learning Model as a step to maximize student learning outcomes in the classroom. By forming heterogeneous groups to carry out Natural and Social Science practice activities on artificial vegetative plant propagation, students are more active and can provide group results that are inventions. As a result, students were able to show an increase in learning outcomes well, from 81.5% in the first cycle to 92.6% in the second cycle. Conveying the results of group work, discussing, expressing discoveries while practicing, being thorough, appreciating the work of other groups and providing good learning results is proof that by applying the Group Investigation learning model has succeeded in achieving the research goals expected by the author. However, this achievement does not indicate that this is the end of the learning model in the teaching and learning process in schools. Educators should use a variety of more interesting learning models to achieve their desired educational goals and as a way to improve their quality as professional teachers at the elementary school level in Indonesia.